2018
DOI: 10.5897/ajar2017.12896
|View full text |Cite
|
Sign up to set email alerts
|

Gas exchange and yield of Prata-type banana plants with fertilizer sources for organic management

Abstract: The aim of this paper is to evaluate gas exchanges and yield of Prata-type banana plants subjected to fertilizer sources for organic management in soil with improved fertility. Two cultivars ('Dwarf-Prata' and 'BRS Platina'), 5 K 2 O rates (0, 200, 400, 600, and 800 kg ha -1 year -1 ) supplied by cattle manure and Naturalplus ® rock powder, and 2 evaluation times (8:00 am and 2:00 pm) were arranged in a randomized complete block design with 15 replicates. As for production, a randomized block design with 4 cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
2
1
0
Order By: Relevance
“…2), in which the plants better intercepted the solar radiation and made use of it, which confirmed the observations of Cayón (2004) and Rodríguez et al (2007), stressing that, in crops planted in rows, the greater penetration of light into the canopy and the degree of absorption of the incident PAR depend on the distances between rows and plants and the planting arrangement. Furthermore, the results are consistent with the report by Rocha et al (2018) for banana 'Prata' and by Santos et al (2015) for banana 'BRS Princesa'. The data also indicated that the Pn and E were directly correlated with the g s , WUE and T i , while the WUE and Pn were inversely associated with the E and T i (Tab.…”
Section: Gas Exchangesupporting
confidence: 92%
“…2), in which the plants better intercepted the solar radiation and made use of it, which confirmed the observations of Cayón (2004) and Rodríguez et al (2007), stressing that, in crops planted in rows, the greater penetration of light into the canopy and the degree of absorption of the incident PAR depend on the distances between rows and plants and the planting arrangement. Furthermore, the results are consistent with the report by Rocha et al (2018) for banana 'Prata' and by Santos et al (2015) for banana 'BRS Princesa'. The data also indicated that the Pn and E were directly correlated with the g s , WUE and T i , while the WUE and Pn were inversely associated with the E and T i (Tab.…”
Section: Gas Exchangesupporting
confidence: 92%
“…The results found in the present research are in agreement with those observed by Marques et al (2018 and. These authors evaluated the effect of the addition of doses of cattle manure and rock powder in the banana trees Prata Anã and BRS Platina and did not observe an increase in production yield during four cultivation cycles.…”
Section: Resultssupporting
confidence: 93%
“…Photosynthesis, transpiration, respiration, growth and development of banana are interdependent and influenced by site, soil and climate conditions (DONATO et al, 2021) and management. Thus, they may be associated with the yield differences between cultivars (TURNER et al, 2007;ARANTES, 2016;RAMOS et al, 2018), when subjected to different irrigation systems (ARANTES et al, 2018), irrigation management strategies (SANTOS et al, 2017), irrigation intervals and emitter heights (LAGE et al, 2020), fertilization with fertilizers for organic management (MARQUES et al, 2018), or to different planting densities (RODRIGUES FILHO et al, 2020), which lead to variations in the total leaf area and leaf area index (LAI). This is important because there is a relationship between LAI and photosynthesis (TURNER et al, 2007), leaf area and yield with varietal specificity for Cavendish (SOTO BALLESTERO, 2008;RODRÍGUEZ GONZÁLEZ et al, 2012), Prata (RODRIGUES et al, 2009) and plantains (CAYÓN SALINAS, 2004).…”
Section: Introductionmentioning
confidence: 99%